Evaluation of off-site effects of wind-eroded sediments especially the content of pesticides: - - Csányi , Katalin; Farsang, Andrea (Geographica Pannonica, 2022)
Wind-eroded sediment, as an environmental transport pathway of toxic elements and pesticids, can result in environmental- and human exposure far beyond the agricultural areas where it has been applied. In our research we quantified the pesticide residues moving in the soil near Szeged (Hungary) on the original soil surface of agricultural areas with a portable wind tunnel. Before the experiments, a portion of the sample area was treated with chlorpyrifos and pendimethalin. A control area was also selected. In 2017-2019, a total of 42 wind event experiments were conducted by examining the topsoil samples. During the experiments, moving soil particals were trapped at various heights (5-10 cm, 20-25 cm and 50-55 cm) and the pesticide concentrates by GC-MS were measured. The enrichment ratios (ER) were calculated, and statistical analyzes were also carried out (SPSS). The measurements obtained that the pendimethalin ER is much higher in the rolled fraction (mean: 13.7) than chlorpyrifos (mean: 2.9). Our measurments showed that the enrichment of chlorpyrifos and pendimethalin can be clearly detected in the rolling and suspended soil particles.
Keywords: wind erosion, chlorpyrifos, pendimethalin, wind tunnel experiment